2016
DOI: 10.15517/lank.v16i2.26014
|View full text |Cite
|
Sign up to set email alerts
|

Main fungal partners and different levels of specificity of orchid mycorrhizae in the tropical mountain forests of Ecuador

Abstract: abStract. Orchids are a main component of the diversity of vascular plants in Ecuador with approximately 4000 species representing about 5.3% of the orchid species described worldwide. More than a third of these species are endemics. As orchids, in contrast to other plants, depend on mycorrhizal fungi already for seed germination and early seedling establishment, availability of appropriate fungi may strongly influence distribution of orchid populations. It is currently debated if green orchids depend on speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Orchids interact with a more limited set of mycorrhizal fungi as compared to other mycorrhizal plants, with a relatively higher degree of specificity for OM than ECM, AM, and even ErM fungi (Dearnaley et al, 2012;van der Heijden et al, 2015;Suárez and Kottke, 2016;Põlme et al, 2018). Mycorrhizal specificity, one of the core issues in OM research, ranges from low to high and can be quantified as the phylogenetic width of the range of associated mycorrhizal fungi (i.e., the ancientness of the last common ancestor).…”
Section: Orchid Mycorrhizal Fungal Specificitymentioning
confidence: 99%
“…Orchids interact with a more limited set of mycorrhizal fungi as compared to other mycorrhizal plants, with a relatively higher degree of specificity for OM than ECM, AM, and even ErM fungi (Dearnaley et al, 2012;van der Heijden et al, 2015;Suárez and Kottke, 2016;Põlme et al, 2018). Mycorrhizal specificity, one of the core issues in OM research, ranges from low to high and can be quantified as the phylogenetic width of the range of associated mycorrhizal fungi (i.e., the ancientness of the last common ancestor).…”
Section: Orchid Mycorrhizal Fungal Specificitymentioning
confidence: 99%
“…Jacquemyn et al (2011b) revealed that the phylogenetic structure of 16 species of the genus Orchis distributed across 11 different regions in Europe can explain the community differences in associated Tulasnellaceae. Many orchid species that are closely related within genera host similar rhizoctonias or Tulasnellaceae operational taxonomic units (OTUs), such as Cypripedium (Shefferson et al, 2007), Goodyera (Shefferson et al, 2010), Neottia (Těšitelová et al, 2015), Teagueia (Suárez and Kottke, 2016), Caladenia (Phillips et al, 2016), Dendrobium (Xing et al, 2017), Pleione (Qin et al, 2019), and Cypripedioideae (lady's slipper subfamily; Shefferson et al, 2019). Therefore, orchid-OMF specific associations during their evolutionary history may result in strong influences of orchid phylogeny on OMF communities.…”
Section: Phylogenetic Signals In Orchid-omf Interactionsmentioning
confidence: 99%
“…While symbiotic fungi are vital for the germination of orchid seeds, the specificity of members of Orchidaceae for their mycorrhizal partners and the effects of the fungi on orchid growth are not perfectly clear. Numerous studies have indicated that Orchidaceae are able to form associations with various fungi (see, for instance 31 33 ). Due to the lack of comprehensive data on myccorhizal symbionts of P. concreta we were not able to include modifications of the availability of fungal components in our analyses.…”
Section: Discussionmentioning
confidence: 99%